Design of a Solar Photovoltaic System for Central Canteen of Delhi Technological University - Kesari, Dr. J.P; Chopra, Sushant; Gupta, Mohit (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Photovoltaics is a method of converting the solar energy contained in the sun to produce electrical energy for use in different applications[1]. The Solar PV system finds applications in many areas of daily needs as well as commercial uses. Some prominent applications are outdoor lighting applications (like roadside flashers, highway safety signs, bus shelters, garden lights and portable lanterns) , telecommunication systems (Mobile towers, Microwave, TV or Radio repeaters, Telemetry stations and Radio telephones) , navigation applications (Railroad signals, buoys, Airport approach systems, offshore oil platforms) , cathodic protection applications (Well heads, oil and gas pipelines), Remote habitat applications (Rural home lighting systems, Remote village electrification, Schools, Hospital & clinics, Cottage industries), Power source for mobile applications (Mobile recreational vehicles, Electric vehicle charging systems, Boats). The solar photovoltaic system mainly consists of solar panels (the main energy conversion stage), MPPT & charge controller stage, battery and an inverter stage to convert the DC power to AC power for subsequent use as most appliances operate on AC. In this study, a design consideration for the solar photovoltaic application in central canteen of Delhi Technological University is presented.